A Review of Community Extension Approaches to Innovation for Improved Livelihoods in Ghana, Uganda and Malawi - Wellard, Kate; Rafanomezana, Jenny; Nyirenda, Mahara; Okotel, Misaki; Subbey, Vincent (The Journal of Agricultural Education and Extension, 2013)
Purpose: Farmer-to-farmer extension offers a potentially low-cost and wide-reach alternative in supporting agricultural innovation. Various approaches are being promoted but information on their impact and sustainability is sparse. This study examines experiences of Self Help Africa and partners in Ghana, Uganda and Malawi. It asks: What is good practice in community extension for agriculture? What has been the impact of community extension on food security for smallholder farmers? What is the potential for scale-up and policy influence? Design/methodology/approach: Findings are based on a three-country mixed methods study of 240 households, farmer groups and community, government and NGO extensionists. Findings: Models of good practice include: community selection of extensionists, a twin technical and community development focus, and mutual learning. Impact of community based extension approaches on uptake of technologies, food security and livelihoods of poor groups was found to be broadly positive. Practical implications: Community based approaches appear sustainable where: communities provide support for their extensionists; community extensionists have marketable skills; communities and extensionists are developing Community Based Organisations (CBOs); and linkages are maintained with research and extension bodies. Community based extension approaches are being scaled-up in Malawi and elsewhere. To achieve sustainable pro-poor impacts, support will be needed for continued technical and community development training and back-stopping for community extensionists, and evaluation of different approaches. Originality/value: The study provides important evidence that community extensionists can help facilitate innovation in sustainable agriculture and reach the poor in a cost-effective way. They should be seen by policy-makers as part of pluralistic demand-driven extension, complementing over-stretched extension services. (Contains 6 tables.)
KerkoCite.ItemAlsoKnownAs: 10.1080/1389224x.2012.714712 10/gf62k8 2129771:3TBPH3VN 2317526:63P23WRI
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Malawi; CA:AandC; CL:de; CL:en; CL:pt; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:R; CT:T; F:learning; F:policy; F:pro-poor; P:agricultural; P:agriculture; P:economy; P:measurement; P:services; P:technology; R:evaluation; R:impact; R:mixed method; T:Training; Z:Agricultural Occupations; Z:Agriculture; Z:Community Development; Z:Community Support; Z:Economically Disadvantaged; Z:Evidence; Z:Food; Z:Foreign Countries; Z:Innovation; Z:Poverty; Z:Rural Education; Z:Rural Extension; Z:Security (Psychology); Z:Sustainability; _C:Benin BEN; _C:Ghana GHA; _C:Malawi MWI; _C:Morocco MAR; _C:Norway NOR; _C:Uganda UGA; _C:United Kingdom GBR; __C:filed:1; __C:scheme:1; publicImportV1